IL-10 rs1800896 Polymorphism: A Risk Factor for Adult Acute Lymphoblastic Leukemia - Abdalhabib EK; Alzahrani B; Saboor M; Hamza A; Elfaki EM; Alanazi F; Alenazy FO; Algarni A; Khider Ibrahim I; Mohamed HA; Hussein Alfeel A; Ali Alshaikh N (Dove Medical Press, 2022)
Ezeldine K Abdalhabib,1 Badr Alzahrani,1 Muhammad Saboor,2- 4 Alneil Hamza,1 Elyasa M Elfaki,1 Fehaid Alanazi,1 Fawaz O Alenazy,1 Abdulrahman Algarni,5 Ibrahim Khider Ibrahim,6 Hozifa A Mohamed,7 Ayman Hussein Alfeel,8 Nahla Ali Alshaikh3,4 1Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, Jouf University, Sakaka, Saudi Arabia; 2Department of Medical Laboratory Sciences, College of Health Sciences, University of Sharjah, Sharjah, United Arab Emirates; 3Department of Medical Laboratory Technology, Faculty of Applied Medical Sciences, Jazan University, Jazan, Saudi Arabia; 4Medical Research Center (MRC), Jazan University, Jazan, Saudi Arabia; 5Department of Medical Laboratory Technology, College of Applied Medical Sciences, Northern Border University, Arar, Saudi Arabia; 6Department of Hematology, Faculty of Medical Laboratory Sciences, Al Neelain University, Khartoum, Sudan; 7Department of Molecular Biology, Faculty of Medical Laboratory Sciences, Al Neelain University, Khartoum, Sudan; 8Department of Medical Laboratory Sciences, College of Health Sciences, Gulf Medical University, Ajman, United Arab EmiratesCorrespondence: Ayman Hussein Alfeel, Department of Medical Laboratory Sciences, College of Health Sciences, Gulf Medical University, Ajman, United Arab Emirates, Email aymanalfeel@gmail.com Muhammad Saboor, Department of Medical Laboratory Sciences, College of Health Sciences, University of Sharjah, Sharjah, United Arab Emirates, Tel +971 56 443 2008, Email msaboor@jazanu.edu.saPurpose: Single-nucleotide polymorphism (SNP) in the promoter region of the IL-10 gene can increase susceptibility to tumor development. The current study aimed to explore the genotypic frequency of interleukin-10 (IL-10) rs1800896 polymorphism in newly diagnosed adult patients with acute lymphoblastic leukemia (ALL) and validate whether this SNP is a risk factor for adult ALL.Patients and Methods: This case-control study was based on a subset of newly diagnosed 154 adult patients with ALL recruited from the Radiation and Isotope Center in Khartoum (RICK) and 154 healthy controls from the same geographical area. Genomic DNA was used for the genotyping of rs1800896 polymorphism through allele-specific polymerase chain reaction (PCR) assays.Results: The genotypic frequencies of rs1800896 showed a statistically significant association of AG and AA genotypes with adult ALL (p< 0.001). Combined genotypes AG+GG vs AA also showed a positive association of rs1800896 with adult ALL (OR=4.89). The allelic frequencies of G and A did not show any significant difference in adult patients with ALL compared with the control group. AG rs1800896 genotype showed an increased risk of B and T ALL (OR=2.51 and 4.70, respectively). Age at diagnosis, gender, and immunophenotype (B vs T ALL) did not exhibit any association of rs1800896 with ALL in this patient group.Conclusion: rs1800896 polymorphism is associated with an increased risk of ALL in adult patients irrespective of the age at diagnosis, gender, and immunophenotype of ALL.Keywords: acute lymphoblastic leukemia, polymorphism, IL-10, - 1082 (A>G), rs1800896